In vitro callus induction and identification of DNA variation in Etlingera elatior using Inter-simple sequence repeat (ISSR) markers - Norsalsabila Mohd Rosli; Muhamad Fahmi Yunus; Tamil Chelvan Meenakshi Sundram; Zarina Zainuddin; Mohd Razik Midin; Md Hoirul Azri Ponari (Ornamental Horticulture)
Etlingera elatior is a promising ornamental horticultural species with various purposes such as medicinal, antibacterial agent, culinary, ornamental, and floral arrangement. The increasing demand for more variation has led to the improvements of E. elatior via tissue culture technology. Somaclonal variation helps to overcome the lack of variation of this species due to asexual propagation. The aims of this study are to induce callus and shoot and to detect genetic variations using ISSR markers. The results showed that the Murashige & Skoog (MS) basal medium supplemented with glucose and 1.5 mg L-1 6-benzylaminopurine (BAP) and 3 mg L-1 2,4-dichlorophenoxyacetic acid (2,4-D) produced significantly higher callus percentage, 50% after 20 weeks of culture. The friable calluses were then transferred to shoot induction media containing different concentrations of different BAP, 1-naphthaleneacetic acid (NAA) and thidiazuron (TDZ). After 12 weeks in shoot induction media, a root-like structure was observed in calluses masses T11 (0.1 mg L-1 NAA and 0.3 mg L-1 TDZ). Seven ISSR primers were used to evaluate the genetic variation of calluses. Seventy-two bands were generated, of which 51 bands were polymorphic with an average percentage of polymorphic bands of 72%. Jaccard’s coefficient of similarity values recorded between 0.3529 and 0.4762 exhibited the level of genetic variation among calluses. In short, the explants were affected by different concentrations of auxin and cytokinin for callus induction. ISSR markers revealed the occurrence of genetic variation during callus and shoot induction processes, suggesting a potential to generate new variants using tissue culture.